Neurosurgery compared to orthopedic spine consultation: A single level I trauma center experience - Shaina Sedighim; Brynn Sargent; Areg Grigorian; Christina Grabar; Anvesh R. Macherla; Michael Oh; Yu-Po Lee; John Scolaro; Jefferson Chen; Jeffry Nahmias (Brain and Spine)
Introduction: Both Orthopedic Surgery (OS) and Neurosurgery (NS) perform spine surgery in the setting of trauma. However, it is unknown whether outcomes differ between these specialties. This study compares management and outcomes for vertebral fractures between NS and OS, hypothesizing similar operation rate, length of stay (LOS), and readmission. Research question: Do outcomes differ between NS and OS in the management of vertebral fractures following trauma? Methods: A retrospective single-center study was conducted on adult patients with cervical, thoracic, lumbar, and sacral fractures treated at a single trauma center, where no standardized pathway exists across NS and OS. Patients were compared for injury profile, diagnostic imaging, and operative techniques as well as LOS, mortality, and complications. Results: A total of 630 vertebral fracture patients (OS:350 (55.6%); NS:280 (44.4%)) were included. NS utilized magnetic resonance imaging (MRI) more commonly (36.4% vs. 22.6%, p < 0.001). NS patients more often underwent operation (13.2% vs. 7.4%, p = 0.016) despite similar fracture number and severity (p > 0.05). Post-operative complications, LOS, and readmission rates were similar between cohorts (p > 0.05). Discussion and conclusion: Despite similar injury profiles, NS had higher rates of MRI usage and operative interventions in the context of traumatic spine fractures. Despite differences in management, major clinical outcomes were similar between NS and OS. However, we do call for further standardization of evaluation and treatment of patients based on established algorithms from such as the AOSpine Thoracolumbar Spine Injury Classification System (ATLICS).